Analysis of satisfaction levels of the business and industrial world on the quality of graduates of the tourism department politeknik negeri bali - Sari, I Gusti Agung Mas Krisna Komala; Kanah, Kanah; Sadguna, I Gde Agus Jaya (Journal of Business on Hospitality and Tourism, 2022)
The purpose of this study was to analyse the satisfaction of graduates of Tourism Department Politeknik Negeri Bali. The source of data comes from the results of the questionnaire distributed to 72 companies as using Slovins’ technique, using the technique probability sampling with simple random sampling. The method of analysis was used the Importance Performance Analysis (IPA) technique with step validity test, reliability test, Importance Performance Analysis and measure Consumer Satisfaction Index. The satisfaction level of the graduates of the Tourism Departement Politeknik Negeri Bali was divided into two attributes, namely soft skill and hard skill consisting of 20 variables with the value of all positive gaps that show into 4 quadrants. The attribute in the III quadrant is GPA > 3.0 (Q20). To the value of Customers Satisfaction Index was 92.81% for soft skills and 93.43% for hard skills. It is categorized very satisfactorily.